Pengaruh Diameter Pipa Primer Pada Irigasi Tetes Bertingkat - Negara, I Dewa Gede Jaya; Hartana, Hartana; Supriyadi, Anid; Saadi, Yusron; Yasa, I Wayan; Julio, Ryan Bagus (LPPM Universitas Mataram, 2024)
Multilevel drip irrigation is an irrigation method that supports water-saving agricultural activities in limited areas by channeling water through perforated pipes from emitters. An ideal multilevel drip irrigation system can provide the same volume of droplets to plants, so that the distribution of irrigation water and the uniformity of drip irrigation are important factors that need to be considered when using drip irrigation to provide plant irrigation. This research aims to determine the effect of using variations in the diameter of PVC pipes as primary pipes on the distribution of drip irrigation and its uniformity. The primary irrigation network tested for each network to the 1st floor to the 3rd floor consists of Â½